The recent expansion of Chilean recluse Loxosceles laeta (Nicolet) (Arachnida: Araneae) in Southern Patagonia - Faundez, Eduardo; Alvarez-Munoz, Claudia X.; Carvajal, Mariom A.; Vargas, Catalina J. (My University, 2020)
The recent expansion of the Chilean recluse Loxosceles laeta (Nicolet, 1849) in southern Patagonia is commented and discussed in the light of current global change. New records are provided from both Region de Aysen and Region de Magallanes. In addition, Isla Dawson in Magallanes is the southernmost record for a sicariid spider in South America. Identification tips for health providers are included.
Keywords: distribution; faunistics; new record; spider